The Heath Introduction to Fiction - Smith A. Paul (Toronto D.C. Heath and Company, 1992)
The fifth edition of this best-selling anthology of more than 60 short stories includes features that make it better choice for your course.o this edition, including Jewetts
Keywords: Literature